2019
DOI: 10.23887/leju.v2i1.20273
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perception in Using Technological Pedagogical Content Knowledge in Teaching English at Senior High Schools in Buleleng Sub-District

Abstract: This study is aimed at investigating English teachers' perception in using Technological Pedagogical Content Knowledge (TPACK) framework in teaching and learning process at Senior High schools in Buleleng Sub District. This study applied an explanatory sequential mixed method design which used a questionnaire and interview guide as the instruments that had been tested for their validity and reliability. The data from the questionnaires were processed by using a Microsoft Office Excel to calculate the mean scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The explanations above show how the student-teachers perceive TPACK and how it can be really important to perceive TPACK positively. In this case, the researcher finds out this study shows similar results to previous research conducted by Prasetya et al, (2019) which also shows positive results regarding the perception of pre-service teachers who teach English. The study results indicate that respondents have a good perception of the implementation of TPACK in English instruction which has a good impact on conveying information from teachers to students in the classroom by applying the TPACK model.…”
Section: Findings and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The explanations above show how the student-teachers perceive TPACK and how it can be really important to perceive TPACK positively. In this case, the researcher finds out this study shows similar results to previous research conducted by Prasetya et al, (2019) which also shows positive results regarding the perception of pre-service teachers who teach English. The study results indicate that respondents have a good perception of the implementation of TPACK in English instruction which has a good impact on conveying information from teachers to students in the classroom by applying the TPACK model.…”
Section: Findings and Discussionsupporting
confidence: 85%
“…The TPACK framework in the teaching process seems to be closely related to teachers' perceptions in teaching English. Prasetya et al (2019) conducted research that aims to determine English teachers' perceptions using the TPACK framework in the teaching process at senior high schools. In this study, the researchers found that most teachers had The Art of Teaching English as a Foreign Language positive perceptions of using the TPACK framework in teaching English in high schools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation